The Role of Fibroblast Growth Factor Receptor 3 (FGFR3) and Androgen Receptor (AR) in a Non-invasive Urothelial Carcinoma Recurrences - Oki Meilani Dewi; Sri Suryanti; Bethy Suryawathy Hernowo (Universitas Islam Bandung, 2019)
Urothelial carcinoma is a bladder carcinoma that took place in the urinary tract. Non-invasive urothelial carcinoma patients have high recurrence rates (50–70%). The recurrences took so many years that may lead to the high-cost treatment and low survival rate. Fibroblast growth factor receptor 3 (FGFR3) and androgen receptor (AR) known to play a role in non-invasive urothelial carcinoma and potentially act as a prognostic marker to predict recurrences. This study aimed to discover the role of FGFR3 and AR in recurrences of non-invasive urothelial carcinoma. This research used a case-control study design. Samples took from patients diagnosed with non-invasive urothelial carcinoma registered at Dr. Hasan Sadikin General Hospital Bandung 1 January 2010–30 December 2015 period. Sixty samples consisted of 30 recurrent groups, and 30 non-recurrent groups individually fixated and embedded to paraffin block for FGFR3 and AR immunohistochemistry analysis. Analysis chi-square performed with a level of confidence 95% and statistical power 95%. p values<0.05 were considered to be statistically significant. Statistical analysis showed that FGFR3 immunoexpression was found significantly low on the recurrence group (p=0.002, OR=5.50). While AR immunoexpression was found insignificant (p=1.000, OR=1.00). FGFR3 immunoexpression from samples in the recurrent group with multiple tumors found to be significantly low (p=0.031, OR=6.067). This study showed that recurrences took place when FGFR3 lowly expressed within non-invasive urothelial carcinoma samples with multiple tumors. This finding may raise a candidate to early-predict the recurrence, thus will suggest early therapy.PERANAN FIBROBLAST GROWTH FACTOR RECEPTOR 3 (FGFR3) DAN RESEPTOR ANDROGEN (RA) TERHADAP KEJADIAN REKURENSI PADA KARSINOMA UROTELIAL BULI NON-INVASIFKarsinoma urotelial merupakan karsinoma buli yang sering terjadi pada saluran kemih. Karsinoma urotelial dibagi menjadi karsinoma urotelial non-invasif dan invasif. Pasien karsinoma urotelial non-invasif mempunyai kejadian rekurensi tinggi (50–70%) dan membutuhkan waktu lama untuk memantau kejadian rekurensi sehingga membutuhkan biaya tinggi dengan angka ketahanan hidup rendah. Fibroblast growth factor receptor 3 (FGFR3) dan reseptor androgen (RA) berperan dalam terjadinya karsinoma urotelial non-invasif dan berpotensi sebagai penanda prognostik yang memprediksi rekurensi secara akurat. Tujuan penelitian ini mengetahui peranan FGFR3 dan RA terhadap kejadian rekurensi pada karsinoma urotelial non-invasif. Penelitian menggunakan rancangan case-control study. Sampel berupa blok parafin yang diagnosis sebagai karsinoma urotelial non-invasif di RSUP Dr. Hasan Sadikin Bandung periode 1 Januari 2010–30 Desember 2015. Sebanyak 60 sampel dievaluasi terdiri atas 30 sampel kelompok rekurensi dan 30 kelompok tidak rekurensi. Pemeriksaan imunohistokimia menggunakan antibodi FGFR3 dan RA. Analisis menggunakan uji chi-square dengan taraf kepercayaan 95% dan kuasa uji (power test) 95%. Nilai p<0,05 dianggap signifikan secara statistik. Pada analisis statistik, imunoekspresi FGFR3 rendah signifikan pada kelompok rekurensi (p=0,002; OR=5,50) dan imunoekspresi RA tidak signifikan (p=1,000; OR=1,00). Imunoekspresi FGFR3 rendah dengan tumor multipel signifikan pada kelompok rekurensi (p=0,031; OR=6,067). Hasil penelitian menunjukkan bahwa rekurensi terjadi ketika FGFR3 terekspresi rendah pada sampel karsinoma non-invasif dengan tumor multipel. Hal ini dapat menjadi penanda memprediksi kejadian rekurensi sehingga dapat dilakukan terapi yang lebih cepat.